Potential classroom stressors of teachers: An audiovisual and physiological approach. (October 2021) - Junker, Robin; Donker, Monika H.; Mainhard, Tim
Abstract: The number of teachers leaving their professions due to high levels of stress is a growing worldwide concern. Previous psychological and physiological research has already identified potential classroom stressors: low student engagement and motivation, negative teacher-student relationships and interactions, as well as teacher-centered activities. The current study extends this research by examining the frequency and intensity of these stressors during actual classroom teaching. The heart rates of 40 teachers were recorded throughout one real-life classroom lesson as a proxy for teacher stress. Heart rate measurements were used to select potentially stressful and non-stressful classroom situations. We transcribed the interactions during these situations and coded the stressors according to the previously mentioned stressor categories. Multilevel regression analyses were conducted to predict teachers' heart rates based on the occurrence of classroom stressors. Students' low engagement and motivation, as well as teacher-centered activities, significantly predicted an increased heart rate. However, pronounced differences were observed between teachers in what they experienced as stressful. This points to significant individual differences in teacher stress triggers and processes. Implications for research and practice are discussed. Highlights: Previous studies found various classroom stressors for teachers. Teacher stress is measured by heart rate. Classroom situations is coded by a deductive coding scheme. Teacher-centered activities and low engagement significantly predict stressful situations. The impact of teacher-centered activities on teacher stress shows most variance.